(untitled) (Social Science Review, 2023)
Urban Rooftop gardening (RTG) as a possible solution to food insecurity gets popularised due to the reduction of urban agricultural land and regarded as an effective climate change impact mitigation strategy. This paper identified the spatio-temporal changes of RTG practices in Dhaka Metropolitan Area (DMA) between 2016 and 2021. This evidence-based study was conducted based on manually extracted build-up (building rooftop) areas of DMA for 2021 and RTG areas of DMA for 2016 and 2021 through digitization from Google earth images using Google Earth Pro software. It is identified that the different zones of DMA experience changes in RTG differently based on their zonal development stages. The DMA received moderate increase (i.e. 15 percent) in RTG between 2016 and 2021 where the western part has greater RTG area than the eastern part. The study also reveals that planned residential areas have higher RTG areas than any other landuse whereas most Government/ Non-Government buildings have less RTG throughout the 20 zones of DMA and the Dhaka Cantonment area. Social Science Review, Vol. 40(1), Jun 2023 Page 129-150